Genomic adaptations to aquatic and aerial life in mayflies and the origin of insect wings - Isabel Almudi (Nature Portfolio, 2020)
Genomic studies of paleopteran insects, such as mayflies, are needed to reconstruct early insect evolution. Here, Almudi and colleagues present the genome of the mayfly Cloeon dipterum and use transcriptomics to characterize its adaptations to distinct habitats and the origin of insect wings.